Nanostructures and Thermal Properties of the Binary Mixture of DNA and a Zwitterionic Phospholipid in the Bulk - Wu, Ching-Mao; Lin, Szu-Yin (Journal of Applied Solution Chemistry and Modeling, 2012)
The mixtures of polyanionic DNA and zwitterionic phospholipids (ZL) have recently received much attention because of their potential for use as vectors in gene therapy or as a template for nanostructure construction. The past few studies on DNA-ZL system were carried out in their aqueous solutions and it was reported that a small fraction of DNA was capable of binding to zwitterionic lipids. However, it is still not known whether, as in the aqueous state, the DNA will be still intercalated between lipid bilayers in the bulk state. In the present study, we examined the DNA-ZL interactions in the bulk state by investigating a binary system composing of DNA and a zwitterionic lipid, 1,2-di(cis-9-octadecenoyl)-sn-glycero-3-phosphocholine (DOPC). The nanostructures and thermotropic phase behavior of this system were investigated using small angle X-ray scattering (SAXS) and differential scanning calorimeter (DSC), respectively. Our SAXS with one-dimensional correlation function results revealed that, as in the aqueous state, the DNA/DOPC bulk mixture forms a multilamellar phase, where the DNA was confined between the DOPC lipid bilayers. The thickness of the hydrophobic layers composed of lipids tails was greater in the DNA-DOPC mixture than in the pure DOPC. However, interestingly, the thickness of the hydrophilic layer composed of lipid headgroups in the DNA-DOPC mixture was same as in the pure DOPC even though in the former DNA was intercalated in this layer. Furthermore, according to the DSC endotherms we also observe that DNA induced a significant depression of gel-to-liquid crystalline phase transition temperature of DOPC bilayer. A thermodynamic model was presented that described the experimentally observed morphological and thermotropic phase behavior.